Integrating agroecology into local development plans in the Fatick department - Piraux, Marc; Sourisseau, Jean-Michel; Sene Mame, Birame (2024)
To encourage a better understanding of the territorialization of agroecology, and with the aim of continuing to promote the agroecogical transition in the department of Fatick, DYTAEL organized, in partnership with ARD, ISRA and CIRAD, several working days with departmental and communal elected officials to consider concrete ways of integrating AE into local plans, both the Departmental Development Plan (PDD) and the Communal Development Plans (PDC).